ANALYSIS OF INCLUSIVE EDUCATION IMPLEMENTATION AT SD PANGUDI LUHUR XAVERIUS SEMARANG CITY - Kavina, Hufadz Nadiyya; Astuti, Tri (Jurnal Gentala Pendidikan Dasar, 2026)
The purpose of this research is to analyze the implementation of inclusive education in classes 2B and 3B at SD Pangudi Luhur Xaverius, Semarang City, with a focus on learning strategies to meet the diverse needs of students, challenges in creating a conducive learning environment, and the efforts of teachers to overcome these challenges. Using qualitative research methods with a case study type, data were collected thru interviews with the principal, class teachers, and students of classes 2B and 3B, observations, and documentation. The data validity technique used is source triangulation by comparing information from different sources with the aim of obtaining a more comprehensive data conclusion. The data analysis technique used is data collection thru interviews, observations, and documentation, data reduction, data presentation, as well as conclusion and verification. The research results show that teachers implement constructivist-based learning thru adaptive learning media, peer tutoring, and differentiation of content, process, and product. Teachers face obstacles in implementing inclusive education, such as creating a conducive learning environment and simultaneously meeting the diverse learning needs of students. To overcome these obstacles, teachers make efforts by collaborating with regular students to become peer tutors for special needs students and integrating techniques or teaching methods that support task differentiation for special needs students. Based on the research findings, the implementation of inclusive education demonstrates good constructivist practices, but systemic support is still needed for sustainability.